Isolated pulmonary haemorrhage after electric shock: a rare phenomenon - Devendra Kumar Singh; Gaurav Pandey; Syed Haider Mehdi Rizvi; Pankaj Kumar Singh (Monaldi Archives for Chest Disease, 2023)
Any type of contact with electricity of low or high voltage can cause injury to the human body with a variable effect on the body. Low-voltage injury is quite common worldwide, there is very less information present in the available literature. The degree of organ damage depends on many factors, which include the duration of electric current exposure, current type, and nature of the affected tissue. The most common presentations are muscle injury, hyperkalemia, pulmonary oedema, and rarely isolated diffuse pulmonary haemorrhage. We present a case of bilateral pulmonary haemorrhage due to electric shock with no visible signs of damage to the chest wall when exposed to a 220 V shock. The diagnosis was confirmed by fresh hemoptysis, chest imaging that showed bilateral perihilar ground glass opacities, and bronchoscopy findings. Given a life-threatening condition, a timely diagnosis is required as massive haemoptysis can occlude the airways leading to hypoxia and mortality.